Relocated memories : the Great Famine in Irish and diaspora fiction, 1846-1870 - Corporaal, Marguérite (Irish studies (Syracuse, N.Y.), 2017)
"The Great Famine radically transformed Ireland; nearly one million people of the rural countryside died, and the eviction of farmers led to massive emigration. The Famine encouraged anti-English, nationalist sentiments, and this trauma is seen as pivotal in the development of an Irish anticolonial consciousness and in the identity formation of transatlantic Irish communities. The Famine also left its undeniable imprint on Ireland's cultural legacies, both at home and in the diaspora. In Relocated Memories, Corporaal challenges the persistent assumption that the first decades after the Great Irish Famine were marked by a pervasive silence on the catastrophe. She uncovers a vast corpus of fiction that consciously addresses the harrowing memories of recent starvation. These novels, novellas, and stories were often published in Ireland, but a large body of this fiction was also written by Irish American and Irish Canadian immigrants and their descendants. Discussing works by well-known authors such as William Carleton and Anthony Trollope as well as more obscure texts by, among others, Dillon O'Brien, Susanna Meredith, Anna Dorsey, and Henry J. Monahan, Corporaal charts the reconfigurations of memory in fiction across generations and national borders. In doing so, she succeeds in bringing significant literary expressions of the tragedy back to the attention of scholars and provides a wider vista of literary Famine memories"--Publisher description